REVISED RARE EARTH ELEMENTS COMPOSITION OF MOCS METEORITE USING HR-ICP-MS AND ICP-QMS ANALYSIS - TĂNĂSELIA, Claudiu; CADAR, Oana; CÂMPEANU, Mara; BALICA, Constantin; DIPPONG, Thomas (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Rare earth elements composition of Mocs meteorite was analyzed using two inductively coupled plasma mass spectrometry methods: a quadrupole and a single-detector sector-field high-resolution instrument. The obtained results are in good agreement with previous studies found in literature for both Mocs and chondritic materials analysis regarding REE composition. Allende meteorite reference material was used for calibration. Sample preparation for ICP-MS analysis was carried out following a custom protocol derived from the literature: the samples were finely ground, then treated in a multi-step procedure [1]. A mix of hydrofluoric acid, nitric acid and perchloric acid was used to digest the sample, which was finally dissolved in nitric acid and diluted accordingly, before being measured directly by ICP-MS instruments. Mocs samples were made available from the Museum of Mineralogy of Babeș-Bolyai University, Cluj-Napoca, and Allende meteorite reference sample was provided by the Smithsonian Institution (split 7, position 17) [2].